LITERASI DIGITAL KEAGAMAAN AKTIVIS ORGANISASI KEAGAMAAN DI MADRASAH ALIYAH NEGERI (MAN) DI KOTA BANDUNG - Mahmudah Nur (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
The development of information technology has not only brought positive values in communication behavior but also a negative impact on digital literacy such as the spread of hoaxes, terrorism, and cyberbullying. Youth group is the most vulnerable group exposed to the bad influence of digital media. This paper presents the result of research on the religious digital literacy of religious organizations activism at the state Islamic senior high school (MAN) in Bandung. This study aims at knowing the digital literacy ability of religious organization activism at these schools in Bandung. This research is a quantitative study which uses questionnaire as a method of collecting data. The findings of this study show that the digital literacy of religious organization activism at the state Islamic senior high school (MAN) in Bandung is at the level of finding, using, and disseminating obtained religious information accessed through websites for the purpose of preaching. Social media is a digital platform often accessed and preferred by students instead of general and religious knowledge websites. Motivation of students in choosing these websites is because they like to search information as entertainment, easiness to visit, lots of choices, interesting languages, images and illustrations.